Arab Americans' Confidence in Police. (May 2015) - Sun, Ivan Y.; Wu, Yuning
Although the September 11 attacks have drawn much law enforcement attention to Arab Americans, research on Arab Americans' perceptions of police is almost nonexistent. Using survey data collected from 850 Arab Americans who resided in the Detroit metropolitan area, this study empirically examined the effects of demographic characteristics, personal experience, social attitudes and values, and social trust, of confidence in local police. The results indicated that the majority of Arab Americans had a great deal or a lot of confidence in police. Arab Americans' confidence in police was significantly related to their social attitudes and trust, such as conservative outlook, confidence in the legal system, respect for authority, and trust in neighbors. Arab Americans' background characteristics and experience had a weak effect on their confidence in police. More empirical research is warranted to assess Arab Americans' evaluations of local police along more indicators of police performance.